2012
DOI: 10.1007/s10346-012-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall-triggered large landslides on 15 December 2005 in Van Canh District, Binh Dinh Province, Vietnam

Abstract: Landslides are one of the most dangerous hazards in Vietnam. Most landslides occur at excavated slopes, and natural slope failures are rare in the country. However, the volume of natural slope failures can be very significant and can badly affect large areas. After a long period of heavy rainfall in the fourth quarter of 2005 in Van Canh district, a series of landslides with volumes of 20, 000-195,000m 3 occurred on 15 December 2005. The travel distances for the landslides reached over 300-400m, and the land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Furthermore, total surface radiation is the sum of direct solar radiation and diffuse solar radiation, and it indirectly influences the probability of landslide occurrence by affecting the aboveground vegetation and soil moisture [54]. The population density index affects landslide evolution indirectly by calculating human engineering activity [55].…”
Section: Appl Sci 2019 9 X For Peer Review 5 Of 18mentioning
confidence: 99%
“…Furthermore, total surface radiation is the sum of direct solar radiation and diffuse solar radiation, and it indirectly influences the probability of landslide occurrence by affecting the aboveground vegetation and soil moisture [54]. The population density index affects landslide evolution indirectly by calculating human engineering activity [55].…”
Section: Appl Sci 2019 9 X For Peer Review 5 Of 18mentioning
confidence: 99%
“…The total surface radiation, defined as the sum of direct and diffuse solar radiation received on the horizontal surface, affects the hydrological environments and land cover types of the slope [59]. Population density, which represents the population in a certain area, mainly plays an important role in human construction activities [60].…”
Section: Land Cover Factors Acquisition From Google Earth and Landsatmentioning
confidence: 99%
“…Rainfall: In almost all the inventoried landslides long duration of rainfall with varying intensities prior to the event was perceptually reported to trigger and is also cited as the main trigger for landslides in Tanzania, East Africa and the world at large [18,46,47]. Generally, the central, western, southeastern and southwestern parts of the country, constituting 75% of the country's land area, receive unimodal rainfall pattern while the northwestern and northeastern parts receive bi-modal pattern [48].…”
Section: Triggering Factors For Landslide Occurrencementioning
confidence: 99%
“…Unusual sounds and flashlights associated with landslide events reported in this inventory have also been reported in landslide events occurring in other parts of the world. For example, Duc [47] reported on loud booming noises, signifying forthcoming severe earthquake or the "angry angel of mountain associated with large landslides in Van Canh District, Binh Dinh Province, Vietnam. Ludwin et al [59] reported on the "A'yahos", a supernatural spirit power in form of a two-headed serpent, which is associated with earth shaking and rushes of turbid water, locally associated with five landslide locales along the trace of the Seattle Fault in USA.…”
Section: Community Perception Of Landslides and Disaster Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation